Credit risk and bank performance: a Sub-Saharan African perspective - Yahaya, Adamu; Mahat, Fauziah; Mamman, Aliyu (Inderscience Publishers, 2024)
Credit risk is one of the dominant risks that pose a great threat to the performance of banks. This study examines the effect of credit risk on the performance of banks in Sub-Saharan Africa (SSA). A total sample of 50 banks was drawn from six Sub-Saharan African countries which include Nigeria, Ghana, South Africa, Zambia, Kenya, and Tanzania from 2010–2018. A two-step system GMM is applied and the findings reveal a significant negative relationship between credit risk and bank performance in the SSA region. The risk committee has a significant positive impact on the performance of banks in the SSA region. Bank management is encouraged to embrace a modern and efficient credit risk management technique to have better control of the rate of credit risk experienced in banks. Copyright © 2024 Inderscience Enterprises Ltd.